1998
DOI: 10.1266/ggs.73.377
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of multi-alien chromatins carrying different powdery mildew-resistant genes from rye and Haynaldia villosa into wheat genome.

Abstract: Powdery mildew-resistant wheat lines, Tra.R9002 with rye chromatin and Tra.V149 with Haynaldia villosa chromatin, were crossed to combine their different powdery mildew-resistant genes in the wheat genetic background. In the F 5 generation of Tra.R9002 × Tra.V149, a highly powdery mildew-resistant line W159 was selected according to its chromosome number 2n = 41 ~ 42. In the F 6 line W159-9 which was immune to powdery mildew, one pair of rye chromosomes and one pair of wheat-H. villosa translocated chromosomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Like RAPD or RFLP, it has been shown to be an efficient tool for detecting of alien chromatin in sexual wheat-H. villosa hybrids (Chen et al 1995a(Chen et al , 1996aShang et al 1997;Yu et al 2001a;Yuan et al 1998), and in hybrid calli and plants obtained from intergeneric somatic hybridization (Zhou and Xia 2005). As in the case of RFLP, GISH can be used for precise determining of breakpoints of translocated chromosomes (Chen et al 1995a(Chen et al , b, c, 1996aMinelli et al 2005;Zhang et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like RAPD or RFLP, it has been shown to be an efficient tool for detecting of alien chromatin in sexual wheat-H. villosa hybrids (Chen et al 1995a(Chen et al , 1996aShang et al 1997;Yu et al 2001a;Yuan et al 1998), and in hybrid calli and plants obtained from intergeneric somatic hybridization (Zhou and Xia 2005). As in the case of RFLP, GISH can be used for precise determining of breakpoints of translocated chromosomes (Chen et al 1995a(Chen et al , b, c, 1996aMinelli et al 2005;Zhang et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Multicolor GISH revealed rye and H. villosa chromatin in wheat lines carrying powdery mildew resistant genes from these two species. In C-banding conducted after GISH one pair of rye 5R and one pair of wheat-H. villosa 6VS-6AL chromosomes were detected (Yuan et al 1998). By GISH Chen et al (2002) demonstrated powdery mildew resistance associated with 6VS chromosome and found this arm also related to wheat curl mite resistance .…”
Section: Molecular and Cytological Markers In Dasypyrum Villosummentioning
confidence: 99%
“…The subsequent fluorescence in situ hybridization procedure followed the procedures of Tomita (1998), Tomita et al (2008) and Yuan et al (1998). Preparations were treated with 80 μg ml −1 ribonuclease (Sigma) in 2×SSC at 37°C for 1 h, followed by washings in 2×SSC for 5 min and a series of 70%, 95% and 100% ethanol at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The identified wheat-D. villosum translocations lines are 1V/1B (Minelli et al 2005), 6VS/ 6AL (Chen et al 1995a;Yu et al 2001;Yuan et al 1998), T6ALAE6V#2S (Liu et al 1988Qi et al 1995Qi et al , 1999, 6DL/6VS (Li et al 1999; other include chromosomes 4V (long arm) and 5V (long arm) of H. villosa (Qi et al 1999). Chen et al (2002) produced two translocation lines T4VL.3AS and T4VS.4DL.…”
Section: Hybridization Of Dasypyrum With Triticum Speciesmentioning
confidence: 99%